Synthesis and Luminescence Properties of SrGd2O4:Eu3+ Red Phosphors - Jun-Feng Wang; Hao Zu; Chuan-Wen Lin; Shou-Jun Ding; Peng-Yu Shao; Ye Xia (International Journal of Optics)
As one of the important raw materials for LED products, phosphors play an important role. At present, the spectrum of LED phosphors lacks red light, resulting in poor quality of white LED products and a low color rendering index (Ra <80), which affects lighting effects. To solve this problem, we synthesized the SrGd2O4:Eu3+ red phosphor by a high-temperature solid-phase method. The structure and luminescence properties of SrGd2O4:Eu3+ red phosphors were studied by means of X-ray diffraction (XRD) measurements of their emission and excitation spectra, and their spectra were analyzed. We also studied the Eu3+ doping concentration with the best luminous efficiency and the color coordinate of the SrGd2O4:Eu3+ phosphor. The experimental results show that SrGd2O4:Eu3+ is a new red phosphor material that can be used for near-ultraviolet or blue-light excitation and has good practicability.